MODIFIED MASS SELECTION WITHIN CORN SYNTHETIC VARIETY - Baktash, F.Y. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research was undertaken to evaluate five cycles of modified mass selection to improve grain yield in synthetic corn (Zea mays L.) variety IPA-5018. The selection was carried out in spring and fall seasons, during, 2013-2015 using 10% selection intensity. The five populations obtained after selection and the original population were evaluated. The experimental design was a randomized complete block design with five replications. The results were revealed a significant differences among selection cycles in grain yield and some yield components. The cycle five produced highest grain yield (9699.30 kg.ha-1) and increased 34.88% to the original population. The regression of grain yield, number of grains.ear-1 and grain weight to selection cycles were significantly linear and R2 more than 80%. We concluded that the modified mass selection could be used successfully in improving the grain yield and some yield components of corn synthetic varieties.